The exosome encapsulated microRNAs as circulating diagnostic marker for hepatocellular carcinoma with low alpha‐fetoprotein. Issue 10 (13th June 2020) - Ghosh, Suchandrima; Bhowmik, Sayantani; Majumdar, Swagata; Goswami, Avijit; Chakraborty, Joyeeta; Gupta, Subash; Aggarwal, Shaleen; Ray, Sukanta; Chatterjee, Raghunath; Bhattacharyya, Suvendranath; Dutta, Moumita; Datta, Simanti; et al.
Abstract: Diagnosis of hepatocellular carcinoma (HCC) remains challenging to clinicians, particularly in a patient with low alpha‐fetoprotein. Here, in silico, ex vivo and in vitro data were combined to identify liver‐specific exosomal miRNAs as an early diagnostic marker for HCC. Transcriptome profiling for mRNA and small RNA in same HCV‐HCC and normal liver tissues followed by cross‐validation of 41 deregulated miRNAs (log2 FoldChange > 1.5, P adj  < .1) with GEO/TCGA datasets of HCV/HBV related HCC vs normal/adjacent tissue revealed three miRNAs were commonly deregulated (miR‐10b/miR‐21/miR‐182) among all HCC irrespective of viral etiology. Targets of top deregulated miRNAs were identified by TargetScan/miRwalk and validated in mRNA transcriptome data followed by Panther/Gene Ontology enrichment/Cytoscape analysis suggested that targets were mostly from carcinogenesis pathways. Hence, those miRNAs were validated in normal and HCV‐HCC tissues by qRT‐PCR and subsequently in plasma‐derived‐exosomes of both HBV/HCV infected non‐HCC (chronic hepatitis [CH]/liver cirrhosis [LC]) and HCC samples, and in liver‐specific Anti‐Asgr2 immuno‐enriched exosomes. Exosomes were verified using Nanosight/TEM/immune‐blotting with anti‐Alix/anti‐GRP78/anti‐Asgr2. Along with miR‐21‐5p, miR‐10b‐5p/miR‐221‐3p/miR‐223‐3p was found significantly upregulated in the exosome of HCC patients than CH/non‐HCC. The comparable expression pattern was seen in anti‐Asgr2 immuno‐precipitated exosomes. Interestingly, the AFP level was found below 250 ng/mL in about 94% of HCV‐HCC and 62% of HBV‐HCC patients. ROC analysis showed that miR‐10b‐5p + miR‐221‐3p + miR‐223‐3p + miR‐21‐5p could differentiate CH/non‐HCC(CH + LC) from HCC with AUROC: 0.86 (97.5% CI: 0.77‐0.94)/0.80 (97.5% CI: 0.70‐0.89), sensitivity: 74%/58% and specificity: 86%/95% while miR‐10b‐5p + miR‐221‐3p + miR‐223‐3p showed AUROC: 0.84 (97.5% CI: 0.74‐0.94)/0.74 (97.5% CI: 0.63‐0.84), sensitivity: 86%/86% and specificity:66%/53% for low AFP‐HCC vs CH/non‐HCC, respectively, having better sensitivity than the combination of four miRNAs. Multivariate analysis further revealed low Albumin and high miR‐21‐5p as probable independent risk factor for HCC. Abstract : What's new? Several microRNAs have been found to distinguish hepatocellular carcinoma (HCC) from normal individuals. However, the use of miRNAs as HCC biomarkers remains controversial due to disease heterogeneity and instability of circulating free miRNA. Here, in silico, ex vivo, and in vitro data were combined to identify liver‐specific exosomal miRNAs as an early diagnostic marker for HCC. Altered circulating hepatocyte‐specific exosomal miRNAs were a risk factor for HCC development in both hepatitis B virus‐ and hepatitis C virus‐infected patients. Diagnosis of low‐AFP HCC with a combination of exosomal miRNAs may improve the clinical management of these difficult‐to‐diagnose patients regardless of viral etiology.